(untitled) (Scientific journal of the Fergana State University, 2023)
The article tried to develop convenient means, methods and methods of using ethno-pedagogical values in forming a sense of national pride in students. Based on these tools, methods and methods, the organization of pedagogical processes aimed at developing a sense of national pride in students was also highlighted, and an optimal system for forming a sense of national pride in students was developed. Also, general secondary school teachers were given suggestions and recommendations regarding the use of convenient means, methods and methods of using ethno-pedagogical values in forming a sense of national pride in students.